1997
DOI: 10.1089/aid.1997.13.1195
|View full text |Cite
|
Sign up to set email alerts
|

An HIV Type 1 Epidemic among Injecting Drug Users in the Former Soviet Union Caused by a Homogeneous Subtype A Strain

Abstract: Epidemiological data have demonstrated rapid growth of HIV-1 infections among injecting drug users (IDUs) in the Ukraine and Russia, during 1996. Here we describe the results of genetic analysis of isolates derived from 12 HIV-1-infected IDUs in different sites of Russia and the Ukraine. The blood samples were taken within a 1- to 2-month period after the first HIV-1-positive test. The results of the heteroduplex mobility assay as well as gag/env phylogenetic analysis reveal that all sequences belong to gag/en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
39
1
5

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(55 citation statements)
references
References 21 publications
4
39
1
5
Order By: Relevance
“…Until 1995, countries of the FSU experienced only a few hundred cases of HIV-1 infection, most of which were associated with sexual transmissions. The first outbreaks of HIV-1 among IDUs in the FSU were reported in 1995 in southern Ukraine (48), followed by rapid spread of the virus in this risk group in the Russian Federation (3,5) and its neighboring countries Belarus and the Republic of Moldova in 1996 (41,50). In 1997, the virus had spread to the Baltic region, inducing a fast-growing epidemic among IDUs in Latvia and later Estonia (2,15,64).…”
mentioning
confidence: 99%
“…Until 1995, countries of the FSU experienced only a few hundred cases of HIV-1 infection, most of which were associated with sexual transmissions. The first outbreaks of HIV-1 among IDUs in the FSU were reported in 1995 in southern Ukraine (48), followed by rapid spread of the virus in this risk group in the Russian Federation (3,5) and its neighboring countries Belarus and the Republic of Moldova in 1996 (41,50). In 1997, the virus had spread to the Baltic region, inducing a fast-growing epidemic among IDUs in Latvia and later Estonia (2,15,64).…”
mentioning
confidence: 99%
“…Blood samples were derived from 27 IDUs, aged 17 to 32, diagnosed as HIV positive in the period from 1996 to 2002 in the Russian Federation (n ϭ 21), the Ukraine (n ϭ 3), and Kazakhstan (n ϭ 3). All blood samples were obtained with informed consent and under approved human use protocols and were genotyped by using gag/env HMA and sequencing as described previously (4,11,17). Of the 27 virus samples examined, 23 belonged to HIV-1 genetic subtype A, typical of IDU populations in Eastern Europe (4,7), and 4 were the CRF03AB recombinant form (5,25,26).…”
Section: Methodsmentioning
confidence: 99%
“…At present, within the territory of the Russian Federation and a number of other former Soviet Union republics (the Ukraine, Moldova, Belarus, Kazakhstan, Estonia, Latvia, Lithuania, Uzbekistan, Georgia, and Azerbaijan) HIV-1 subtype A variants predominate, circulating among injecting drug users (IDUs) and their sexual partners (3,6,7,23,25,27,31,32,34 (4,5,25). To obtain such information, we analyzed HIV-1 genetic variants, along with conventional sequencing, by using oligonucleotide microarrays that have already been proven to be used as a diagnostic tool for identifying nucleic acid polymorphisms (24,29,41).…”
mentioning
confidence: 99%
“…This would be expected to be associated with a greater degree of evolution than the rapid spread associated with intravenous drug use. 32,33 Thus it has been shown that HIV-1 evolves less among intravenous drug users than among heterosexuals. 32 This has also been observed in the context of CRF01_AE in northern Vietnam and Southern China since the 1990s to more recently.…”
Section: Hiv-1 Env Sequences In Pregnant Women In Vietnamcan Be Identmentioning
confidence: 99%
“…32,33 Thus it has been shown that HIV-1 evolves less among intravenous drug users than among heterosexuals. 32 This has also been observed in the context of CRF01_AE in northern Vietnam and Southern China since the 1990s to more recently. 5,6,21,30 The analysis of synonymous and nonsynonymous nucleotide changes indicated that the maternal sequences had evolved when comparing them to the older sequences from northern Vietnam.…”
Section: Hiv-1 Env Sequences In Pregnant Women In Vietnamcan Be Identmentioning
confidence: 99%